1986
DOI: 10.1007/bf00392322
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport across the plasmalemma of Lemna gibba G1

Abstract: Lemna gibba L., grown in the presence or absence of Fe, reduced extracellular ferricyanide with a V max of 3.09 μmol · g(-1) fresh weight · h(-1) and a K m of 115 μM. However, Fe(3+)-ethylenediaminetetraacetic acid (EDTA) was reduced only after Fe-starvation. External electron acceptors such as ferricyanide, Fe(3+)-EDTA, 2,6-dichlorophenol indophenol or methylene blue induced a membrane depolarization of up to 100 mV, but electron donors such as ferrocyanide or NADH had no effect. Light or glucose enhanced fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 30 publications
4
39
0
Order By: Relevance
“…Rubinstein and Stern (1986), Lass et al (1986), and Marrè et al (1988) assume that cytoplasmic acidification due to enhanced electron donor oxidation and the lowered electrochemical gradient across the PM stimulate the ATPase.…”
mentioning
confidence: 99%
“…Rubinstein and Stern (1986), Lass et al (1986), and Marrè et al (1988) assume that cytoplasmic acidification due to enhanced electron donor oxidation and the lowered electrochemical gradient across the PM stimulate the ATPase.…”
mentioning
confidence: 99%
“…We found gM CCCP to have similar effects to those of DCCD on Fe3" reduction and K+ efflux (Tables III and V), which is consistent with the above hypothesis. Inhibition of the reductase activity by CCCP has also been reported in connection with the standard system (14) and with the iron deficiency increased system (2, 4). AWANTARA ET AL.…”
Section: Discussionmentioning
confidence: 87%
“…Our results disagree with that suggestion, perhaps because we used a different e-acceptor: Fe3+-EDTA instead of ferricyanide. Lass et al (14) have found different responses in Lemna gibba depending on the e-acceptor used. When ferricyanide was added, the membrane depolarization in- Anoxia has been found to influence redox system activity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations